1955
DOI: 10.1021/jf60054a008
|View full text |Cite
|
Sign up to set email alerts
|

Wine Production, Skin Pigments of Cabernet Sauvignon Grape and Related Progeny

Abstract: Skin Pigments of the Cabernet Sauvignon Grape and Related ProgenyThe skin pigments of the Cabernet Sauvignon grape have been separated by paper chromatography and identified as malvidin, two glucosides of malvidin, a petunidin glucoside, a delphinidin glucoside, and a complex diglucoside of malvidin. Evidence is presented to indicate that the two malvidin glucosides are the 3-glucoside and the 3,5-diglucoside, and that the delphinidin and petunidin pigments are the 3,5-diglucosides. The malvidin diglucoside wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1959
1959
1980
1980

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…The results of this study agreed partially with those reported by Bockian et al (1955) in that glycosides of delphinidin, petunidin, and 'malvidin were found. However, the state of glucosidation of the compounds found in this study was not the same as those reported by Bockian et al (1955).…”
Section: And Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study agreed partially with those reported by Bockian et al (1955) in that glycosides of delphinidin, petunidin, and 'malvidin were found. However, the state of glucosidation of the compounds found in this study was not the same as those reported by Bockian et al (1955).…”
Section: And Discussionsupporting
confidence: 92%
“…However, the state of glucosidation of the compounds found in this study was not the same as those reported by Bockian et al (1955). Those investigators reported that the most abundant pigment was malvidin-3,5-diglucoside, based on the use of one solvent.…”
Section: And Discussioncontrasting
confidence: 69%
See 3 more Smart Citations